Pengaruh Kualitas Produk Dan Word Of Mouth (WOM) Terhadap Keputusan Pembelian Konsumen Di Meubel UD. Arafah Kota Gorontalo - Abdullah, Karmila; Juanna, Andi; Machmud, Rizan; Hinelo, Raflin; Kango, Umin (Innovative: Journal Of Social Science Research, 2024)
This study researches the impact of item quality and Verbal (WOM) on buyer buying choices at Furniture UD Arafah in Gorontalo City. Essential information were assembled from the clients of Furniture UD Arafah, with an example size of 96 members decided utilizing the Slovin equation. The review decided an example of 96 respondents utilizing the Slovin recipe. Information gathered by means of polls were thoroughly surveyed through legitimacy and unwavering quality tests, old style suspicions, and different direct relapse investigation utilizing SPSS Form 20. The outcomes uncovered that both item quality and Verbal (WOM) decidedly affect purchaser buying choices at Furniture UD Arafah in Gorontalo City. The examination created a coefficient of assurance (R²) of 72.8%, demonstrating that these two elements represent 72.8% of the fluctuation in buying choices. The leftover 27.2% is credited to different factors not investigated in this examination.